Model Perampasan Aset Hasil Tindak Pencucian Uang dalam Kasus Binomo: Terobosan Kekosongan Hukum Perampasan Aset di Indonesia - Dhumillah, Dewic Sri Ratnaning; Hasugian, Yesaya Hasiholan Immanuel (PT Elaborium Elevasi Indonesia, 2023)
An Advances in information technology in the industrial revolution 5.0 have brought major changes and impacts. This also makes the modes of crime increasingly varied, which can be detrimental to the economic stability of society. In February 2022, Bareskrim Polri arrested a number of people who spread fake news using online fraud on the binomo or binary options application where the perpetrators laundered money from the proceeds of the crime. In the legal process of this binomo case, the panel of judges through Supreme Court Decision No. 2029k/Pid.Sus/2023 makes a breakthrough in standards for confiscation and return of assets proceeds from crime to victims amidst the absence of specific regulations to handle confiscation of assets proceeds from crime in Indonesia. For this reason, this research aims to identify the asset confiscation model that is applied to the binomo case to create an ideal confiscation model for the proceeds of money laundering crimes so that it can be applied as an alternative to fill legal gaps. Using normative juridical methods involving theory, legal principles and related legal regulations as well as asset application compliance studies from several countries.